EMPLOYEE WAGE SYSTEM AT THE LEGAL AID AGENCY BANDA ACEH IN REVIEW ACCORDING TO THE CONCEPT OF IJARAH BI AL-'AMAL - M.Ulul Azmi (JURISTA: Jurnal Hukum dan Keadilan, 2017)
This research is motivated by the existence of cooperation between employees and LBH Banda Aceh, where the employees carry out work to the Institute and the Institute is obliged to provide wages in accordance with the work that has been carried out. The issue to be researched is how the employee wage system at LBH Banda Aceh and how the practice of employee wage system at LBH Banda Aceh is reviewed according to the concept of ijarah bi al-'amal. The results of the research found that LBH Banda Aceh has not made a clear work contract, both in terms of the amount of wages and working time. Employees who work are considered the same as those who do not work by the institution, this will certainly harm one party where the other party only enjoys the work of other employees. If at any time there is a wage reduction, the institution does not provide a detailed explanation directly to the employee of the reason for the wage reduction, which results in a lack of transparency between the parties in the institution. As for the view of ijarah bi al-'amal, not everything is in accordance with ijarah bi al-'amal, especially in terms of contract clarity and wage distribution. Those who work and do not work are considered the same without any distinction so that it is not in accordance with the requirements of the object of wages, which must be in accordance with the level of work, as well as the requirement of ujrah which must be known in amount by both parties.